TAILING POND MAINTENANCE SYSTEM PT. DINAMIKA SEJAHTERA MANDIRI AT THE TERAJU SITE, TOBA DISTRICT, SANGGAU REGENCY - Gazhian, Syarif Rafhi; Nirmala, Azwa; Aprillia, Ricka; Sutrisno, H.; Meilasari, F. (Fakultas Teknik Universitas Tanjungpura, 2022)
PT. Dinamika Sejahtera Mandiri has 6 settling ponds. One of the factors that must be considered in mining activities is the residue from the washing process that will enter the settling pond. Pool conditions at PT. The Mandiri Sejahtera Dynamics seems to be almost full, which requires a study on the maintenance of the settling pond to be carried out. This research aims to plan and schedule the dredging of the settling pond and the addition of tools for optimal pond maintenance.The research was conducted by collecting primary and secondary data, primary data consisting of tailings samples, circulation time, and full discharge time. While secondary data consists of rainfall, equipment specifications, pond depth, and pond area. Then it will be processed from the calculation of planned rainfall, rainwater discharge, percent solid, particle velocity, settling material, pond dredging time and the number of additional tools.